Phosphorus Management in Pearl millet-Mustard Cropping System in Coarse Textured Soils in Southern Haryana - Jagdev Singh, P.K. Yadav; M.K. Jat, Abha Tikkoo, S.S. Yadav (Journal of the Indian Society of Soil Science, 2016)
A field experiment was conducted from rabi 2009-10 to kharif 2013 to evaluate the direct and residual effect of phosphorus (P) on crops and also to find out optimum time of application of P in pearl millet-mustard cropping system in a coarse-textured low P status soil. Four levels of P (0, 30, 45 and 60 kg P2O5 ha-1) were evaluated in two sets. In one set, fertilizer P was applied to mustard and its residual effect was studied in pearl millet crop and in other set, the P was applied to pearl millet and its residual effect was studied in mustard crop. Mustard crop responded significantly to direct application of 30 kg P2O5 ha-1 and residual effect of P in pearl millet was significant at 60 kg P2O5 ha-1. Pearl millet responded significantly to direct application up to 60 kg P2O5 ha-1 and residual effect of P in mustard was significant at 60 kg P2O5 ha-1. The benefit:cost ratio of pearl millet-mustard cropping system was higher when P was applied to mustard compared with application of P to pearl millet.